Culture-Based Teaching: Integrating Indonesian Culture in English Language Teaching (ELT) - Nur Fitria, Tira (International Journal of Sustainable English Language, Education, and Science, 2025)
This research describes the integration of Indonesian culture into English Language Teaching (ELT). This research is library research. The analysis shows that integrating Indonesian culture into English learning is crucial supported by the nation's commitment to "Unity in Diversity" and the preservation of cultural richness across all societal sectors including education. This integration deepens students' understanding of English proficiency and Indonesian cultural values. English teachers play a dual role in fostering language acquisition and imparting local cultural insights to cultivate students who appreciate heritage. They can integrate Indonesian culture into ELT including: Firstly, including using Indonesian folk tales, traditional songs, and arts to enhance language skills including vocabulary, grammar, listening, and pronunciation through projects and theater. Analyzing Indonesian films with English subtitles enriches students' cultural comprehension. Secondly, discussions and explorations of Indonesian values and philosophies alongside studies on traditional ceremonies and cuisine, highlight the cultural context within language learning. Practical language skills are honed through everyday use of Indonesian phrases, role simulations in cultural contexts, and integration of Indonesian loanwords into English vocabulary. Thirdly, collaborative projects on cultural festivals, dances, and art exhibitions promote teamwork and deepen cultural understanding through English presentations. Using guest lectures and partnerships with local communities facilitates direct interaction and experiential learning. Fourthly, technology and media are leveraged to explore Indonesian culture in English, using documentaries, social media, podcasts, and student-generated content like podcasts and vlogs to enhance language proficiency and cultural appreciation. Lastly, contextually based evaluations assess students' comprehension of Indonesian culture through simulated interactions, reflective journals, real-life case studies, critical thinking, and practical application of cultural knowledge in English contexts. Integrating Indonesian culture into ELT can enhance language skills across reading, writing, listening, and speaking and develop students' cultural competence. This approach prepares them as culturally sensitive global citizens capable of effective cross-cultural communication and appreciation.